2016
DOI: 10.1002/j.1839-4655.2016.tb00375.x
|View full text |Cite
|
Sign up to set email alerts
|

Recent public policy and Australian older workers

Abstract: This article considers the characteristics and utility of pro-work policies targeting Australian older workers that have emerged in the context of population ageing, amid concerns that this will lead to labour shortages and an increasing social welfare burden. There has been a recent surge in public policy regarding the ageing workforce, the efficacy of which has not been tested by evaluation studies. After considering the conceptual foundations and objectives of various government initiatives, it is argued th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Yet, early retirement has not entirely disappeared from retirement income frameworks, with most OECD countries retaining it in some form (OECD, 2019). In Australia, a range of measures in support of prolonging working lives have been initiated, including the establishment of the role of Age Discrimination Commissioner and the pushing out of the age at which a person can receive the Age [State] Pension (Taylor et al, 2016). However, while under Australian law there are prohibitions concerning compulsory retirement (Patterson, 2004), provision also exists for employers to implement voluntary early retirement schemes.…”
Section: Early Retirement Remains Popular But Is Criticisedmentioning
confidence: 99%
“…Yet, early retirement has not entirely disappeared from retirement income frameworks, with most OECD countries retaining it in some form (OECD, 2019). In Australia, a range of measures in support of prolonging working lives have been initiated, including the establishment of the role of Age Discrimination Commissioner and the pushing out of the age at which a person can receive the Age [State] Pension (Taylor et al, 2016). However, while under Australian law there are prohibitions concerning compulsory retirement (Patterson, 2004), provision also exists for employers to implement voluntary early retirement schemes.…”
Section: Early Retirement Remains Popular But Is Criticisedmentioning
confidence: 99%
“…The ageing of the Australian population has led to much public policy and debate focused on the need to prolong working lives in order reduce welfare costs and to respond to projected shortfalls in labour as large numbers of older workers retire (Taylor et al , 2016). While issues of older people's employment have not solely been considered through an age discrimination lens, in Australia the potential importance of this issue has garnered much attention in recent years.…”
Section: Recent Advocacy Concerning Age Discrimination and Older Peop...mentioning
confidence: 99%
“…(p. 143). Taylor, Earl and Mcloughlin [36] reported that recent evidence appears to indicate a growing acceptance of older workers in response to expected labor shortages and "that significant proportions of employers anticipate an ageing of their workforces" (p, 243). Taylor, Rolland and Zhou [37] provided a useful guide on the employment of older Australian workers that encompasses advocacy actions and approaches for developing a workforce culture that does not discriminate against older workers (see also Ackerman & Kanfer, 2020 [38]; Settles, 2013 [39]; Taylor & Smith, 2017 [40]; Thornton & Luker, 2010 [41]).…”
Section: Rethinking Aging Societies: Facing the Longevity Revolutionmentioning
confidence: 99%